New scale insects (Hemiptera: Coccomorpha) records as mango pests in Northeast Brazil - da Costa-Lima, Tiago Cardoso; Peronti, Ana Lúcia Benfatti Gonzalez [UNESP]; Wolff, Vera Regina dos Santos; Pereira, Elvis Prudêncio de Araújo; Paranhos, Beatriz Aguiar Jordão (Springer Nature, 2022)
This present study aimed to report the scale insects associated on Mangifera indica L. in the Submedium São Francisco Valley, Brazil. Four species were collected: Pseudischnaspis bowreyi (Cockerell), Aulacaspis tubercularis Newstead (Diaspididae) and Ceroplastes floridensis Comstock (Coccidae) on fruits and leaves and Ceroplastes stellifer (Westwood) on leaves. Pseudischnaspis bowreyi is associated for the first time with mango trees in Brazil. Ceroplastes floridensis and P. bowreyi are reported for the first time in the states of Bahia and Pernambuco and C. stellifer in the state of Bahia. All scale insects obtained in this study caused injuries that led to control methods adopted by the growers to reduce their populations, but only A. tubercularis was already reported in the region.
Keywords: Coccidae; Diaspididae; Mangifera indica; Pseudischnaspis bowreyi